Hearing aids with tinnitus sound support reduce tinnitus severity for new and experienced hearing aid users - Sanders, Philip J.; Nielsen, Reena M.; Jensen, Josefine J.; Searchfield, Grant D. (Frontiers in Audiology and Otology, 2023)
Objective This interventional study tested the hypothesis that hearing aids with a tinnitus sound support feature would reduce the impact of tinnitus for both new and experienced hearing aid users over a 12-week trial period. Methods A total of 19 experienced hearing aid users and 21 participants with no previous hearing aid experience completed the study. Hearing aids were fitted and dispensed with tinnitus masking sounds adjusted to individual preferences. The primary outcome measure was the Tinnitus Functional Index (TFI) score change between baseline and the end of the 12-week trial. This trial was registered on the Australian New Zealand Clinical Trials Registry, trial ID: ACTRN12621001754831. Results The TFI scores and secondary measures indicated significant improvements (reductions in tinnitus impact) at the end of the trial compared to the baseline for both experienced and new hearing aid users. Since no group differences were observed, pooled data are presented in this study. The median TFI total score before treatment was 49.0 (IQR = 40.0), and the median TFI total score after treatment was 26.0 (IQR = 26.0). A significant reduction (p = 0.0001) in the total TFI score of 24 points was observed after treatment, producing a large effect size (d = 0.60). Conclusions The results confirm previous findings that hearing aids assist in reducing the impact of tinnitus on daily life. The Oticon miniRITE R combination hearing aids used in this study resulted in similar improvements for both new and existing hearing aid users. This suggests that the tinnitus-reducing effects of these aids were greater than those already being used by participants.